Design of a two-layered scatternet formation (TLSF) protocol for bluetooth ad hoc wireless personal area networks - Valeriano, A. Dasalla, Jr. (Faculty of Computer Science and Information Technology, 2005)
This paper aims to explore the problem scatternet formation in ad hoc wireless personal area networks built on the Bluetooth technology. The issue selection of which nodes become master or slaves and how slaves are assigned masters during the topology formation can have a significant impact on the first connectivity.